Current manufactured cigarette smoking and roll-your-own cigarette smoking in Thailand: Findings from the 2009 Global Adult Tobacco Survey - Sarunya Benjakul (2018)
Background: Current smoking prevalence in Thailand decreased from 1991 to 2004 and since that time the prevalence has remained flat. It has been suggested that one of the reasons that the prevalence of current smoking in Thailand has stopped decreasing is due to the use of RYO cigarettes. The aim of this study was to examine characteristics of users of manufactured and RYO cigarettes and dual users in Thailand, in order to determine whether there are differences in the characteristics of users of the different products. Methods. The 2009 Global Adult Tobacco Survey (GATS Thailand) provides detailed information on current smoking patterns. GATS Thailand used a nationally and regionally representative probability sample of 20,566 adults (ages 15 years and above) who were chosen through stratified three-stage cluster sampling and then interviewed face-to-face. Results: The prevalence of current smoking among Thai adults was 45.6% for men and 3.1% for women. In all, 18.4% of men and 1.0% of women were current users of manufactured cigarettes only, while 15.8% of men and 1.7% of women were current users of RYO cigarettes only. 11.2% of men and 0.1% of women used both RYO and manufactured cigarettes. Users of manufactured cigarettes were younger and users of RYO were older. RYO smokers were more likely to live in rural areas. Smokers of manufactured cigarettes appeared to be more knowledgeable about the health risks of tobacco use. However, the difference was confounded with age and education; when demographic variables were controlled, the knowledge differences no longer remained. Smokers of manufactured cigarettes were more likely than dual users and those who used only RYO to report that they were planning on quitting in the next month. Users of RYO only appeared to be more addicted than the other two groups as measured by time to first cigarette. Conclusions: There appears to be a need for product targeted cessation and prevention efforts that are directed toward specific population subgroups in Thailand and include information on manufactured and RYO cigarettes. © 2013 Benjakul et al.; licensee BioMed Central Ltd.